PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIORAMA TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN PKN DI SDN 4 CAKRANEGARA - Nurmekasari; Nuraihan (Al-mujahidah, 2024)
This research aims to explore the effect of using diorama learning media on increasing motivation and learning outcomes for class III students in Citizenship Education (PKN) subjects at SDN 4 Cakranegara, Mataram City. The method used was Classroom Action Research (PTK) involving 26 students as research subjects. Data was collected through two observation cycles, where the first cycle showed 90% learning implementation with an average learning outcome of 80.62 and classical completeness 88%, while the second cycle recorded 100% implementation with an average learning outcome of 88.90 and classical completeness 92%. The research results showed that the use of diorama media significantly increased students' interaction and understanding of material about cultural diversity, such as traditional clothing, typical food and regional languages. These findings underline the importance of using appropriate learning media to increase the effectiveness of learning in elementary schools.